A feasibility study of the Nativis Voyager® device in patients with recurrent glioblastoma in Australia. (7th February 2019) - Murphy, Michael; Dowling, Anthony; Thien, Christopher; Priest, Emma; Morgan Murray, Donna; Kesari, Santosh
Aim: Evaluation of the Nativis Voyager ®, an investigational medical device, as monotherapy for recurrent glioblastoma (rGBM).Materials & methods:  A total of 15 patients with rGBM were treated with one of two Voyager ultra-low radio frequency energy cognates: A1A or A2HU. Safety and clinical utility were assessed every 2–4 months.Results: Median overall survival was 8.04 months in the A1A arm and 6.89 months in the A2HU arm. No serious adverse events associated with Voyager were reported. No clinically relevant trends were noted in clinical laboratory parameters or physical exams.Conclusion: The data suggest that the Voyager is safe and feasible for the treatment of rGBM.